2017
DOI: 10.1097/md.0000000000006290
|View full text |Cite|
|
Sign up to set email alerts
|

Real role of β-blockers in regression of left ventricular mass in hypertension patients

Abstract: Background: Left ventricular hypertrophy (LVH) is commonly present in patients with hypertension (HT). According to the expert consensus document from American, angiotensin-converting enzyme inhibitor (ACEI) and angiotensin receptor blockers (ARBs) were recommended as 1st-line therapeutic drugs. However, none noticed the different efficacy between fat-soluble and selective b1-receptor blockers (FS-b-B) and other b-blockers on regression of LVH before. The aim of this analysis was to compare the efficacy of FS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Brigitte et al have shown that it takes at least 100 days to reverse this process 70 . Therefore, the shorter intervention period in the previous meta‐analysis was insufficient to evaluate the possibility of reversing LVH with various antihypertensive drugs 61 . Unlike previous meta‐analyses, the shortest observation period in our study was three months, and network meta‐analysis suggested that ARB might be the preferred antihypertensive drug to reverse LVH.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Brigitte et al have shown that it takes at least 100 days to reverse this process 70 . Therefore, the shorter intervention period in the previous meta‐analysis was insufficient to evaluate the possibility of reversing LVH with various antihypertensive drugs 61 . Unlike previous meta‐analyses, the shortest observation period in our study was three months, and network meta‐analysis suggested that ARB might be the preferred antihypertensive drug to reverse LVH.…”
Section: Discussionmentioning
confidence: 57%
“…Prevention or reversal of LVH has been shown to reduce the risk of cardiovascular events in hypertensive patients 59,60 . Although several clinical trials and meta‐analyses have compared the effects of different classes of antihypertensive drugs on ventricular hypertrophy, the usefulness of the results is limited by their inadequate design and inappropriate methods 61,62 . Although meta‐analyses can improve the statistical power and provide more accurate estimates of the effect value, the results depend largely on the criteria for inclusion in the study 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…When LVH regresses to normal level, spontaneously or due to therapy, cardiovascular risk is substantially reduced, independently of levels of blood pressure control. 19 Many factors can contribute to this reversal effects, like blood pressure control, 20 time on dialysis 21,22 use of ACE inhibitors, 23,24,25 ARBs, 23,25,26 β-blockers, 23,25,27 and other antihypertensive drugs. 20,23,27 We had the caution to analyze the frequency of all these features in both groups with very similar results.…”
Section: Discussionmentioning
confidence: 99%
“…19 Many factors can contribute to this reversal effects, like blood pressure control, 20 time on dialysis 21,22 use of ACE inhibitors, 23,24,25 ARBs, 23,25,26 β-blockers, 23,25,27 and other antihypertensive drugs. 20,23,27 We had the caution to analyze the frequency of all these features in both groups with very similar results. We have also analyzed the use of metformin, due to its effect in the reversal of LVH 28 with a frequency of use similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the article, “Real role of β-blockers in regression of left ventricular mass in hypertension patients: Bayesian network meta-analysis”, [1] which appeared in Volume 96, Issue 10 of Medicine , Drs FuWei Xing, Jingzhou Jiang, Anli Tang and Yili Chen should also be affiliated with Key Laboratory on Assisted Circulation, Ministry of Health, Guangzhou 510080, China.…”
mentioning
confidence: 99%